'Russia is all right': British newspaper reporting of the Russian Revolution of February 1917. Issue 4 (1st October 2020) - Rodgers, James
Abstract : This article considers the British newspaper coverage of the February (or March) revolution in Petrograd in 1917. It argues that, on the key question of Russia's continuing as an ally in World War I, the impression which the coverage conveyed to readers was unduly optimistic. It assesses political factors which may have influenced this. It contrasts the optimism of the editorial columns with the correspondents' reports, and argues that, despite political influence, and the difficulties involved in reporting the revolution, correspondents were able to convey vivid impressions of a city in the throes of massive political change. It concludes by suggesting that the desire to believe that Russia would fight on was so strong that it eclipsed other interpretations of events, and meant that readers—including policy makers—were ill prepared for what would eventually come to pass.